Exploring prehospital C2-work during a mass gathering event. Issue 2 (12th October 2015) - Prytz, Erik G.; Rybing, Jonas; Carlström, Eric; Khorram-Manesh, Amir; Jonson, Carl-Oscar
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the workload and shared workload awareness in a staff performing command and control (C2) work during a planned major incident (MI) empirical case in Sweden. Design/methodology/approach – Data on workload and shared awareness were collected during live C2-work using qualitative observations and in-situ interviews mixed with quantitative questionnaires. Findings – A content analysis of the qualitative data revealed categories of workload sources. Quantified workload estimates showed changes in workload levels over time and staff roles, which were also contextualized using the results of the qualitative data. Data on shared awareness indicated that team workload awareness shifted over time according to common patterns. This study demonstrates a promising methodology to study C2-related factors during live EMS work. Research limitations/implications – The observed variations in workload imply that research that relies only on post-task measurements of workload may be inaccurate. Future research could use this method to investigate the connection between workload and performance during different types of MIs. Originality/value – The results can be used to inform future Göteborgsvarvet C2-teams in terms of when, why, and for whom task load changes, which would support predictive allocation of resources.